Inocencia - Fitzgerald, Penelope (Impedimenta, 2014)
Beautiful Chiara is the last of the Ridolfi, a Florentine family of long lineage and eccentric habits. She is smitten with Salvatore, a brilliant but penniless doctor a rational man who wants nothing to do with romance. This is the story of how these two -- with the best intentions, the kindest of instincts, and the most meddlesome of friends -- make each other wonderfully miserable.